Attribution And Accountability: Voting for roads in Ghana. (3rd August 2015) - Harding, Robin
Abstract : Do voters in Africa use elections to hold governments accountable for their performance in office? In contexts of limited information and weak state capacity, it can be difficult for citizens to attribute the provision of public goods and services to political action. As a result, voters often have little information about government performance on which to condition their electoral support. Such contexts are frequently characterized by clientelism or ethnic politics, and there is a widespread impression that African elections are little more than contests in corruption or ethnic mobilization. Using an original panel data set containing electoral returns and detailed information on road conditions throughout Ghana, the author provides robust evidence that when a public good can be attributed to political action, as is the case with roads in Ghana, electoral support is affected by the provision of that good. The author also uses data on a variety of educational inputs to test the claim that votes are conditioned only on attributable outcomes.